Defesa técnica, eficiência e garantismo - Grilo, Fabiano Franklin Santiago (2011)
This paper aims to identify, in light of the Federal Constitution, the content of the right of defense, with a view to consolidating the crucial defense technique in the harvest of the criminal prosecution, seeking skilled design tools in order to promote their effectiveness and efficiency. In the context of a democratic state is the stale technical defense to move away from the whole formal apparatus, which must be equipped with mechanisms capable of disentangling the ballast of a fair and impartial process, is the phase out of court, judicial, or also in phase of enforcement, serving not only to impose limits on state action, but also to provide the citizens of the mechanisms inherent to it. Sees is that the accurate analysis of the institute, in the light of the current conjecture of national law, which increasingly depends on its interpretation in the light of constitutional paradigms in order to become more and more burning of its principles, should lead to fundamental revisit of Article 5 of the Federal Constitution and the sections dealing with the subject, this path trodden under the foundations of the Human Dignity